Facile synthesis of graphene nanoribbons from zeolite-templated ultra-small carbon nanotubes for lithium ion storage. Issue 43 (29th October 2018) - Xu, Xintong; Ruan, Shuangchen; Zhai, Jianpang; Zhu, Haiou; Yu, Li; Pei, Jihong; Cui, Zhe; Zou, Rujia; Hu, Junqing; Lu, Aijiang; Yu, Mingyang; Tang, Zikang
Abstract : Graphene nanoribbons are synthesized by unraveling ultra-small carbon nanotubes, which show high performance for lithium ion storage. Abstract : One-dimensional graphene nanoribbons are attracting considerable attention due to their extraordinary electronic, magnetic, and optical properties, and have a wide range of applications, but have not attained full success owing to the lack of simple and efficient synthetic strategies. Here, we present a facile strategy for the synthesis of graphene nanoribbons by unraveling ultra-small carbon nanotubes. The armchair (2, 2) carbon nanotubes with a theoretical diameter of 0.28 nm fabricated in the nanochannels of zeolite ZnAPO4 -11 (AEL) can be transformed into graphene nanoribbons by removing the AEL template through chemical treatment. The as-synthesized graphene nanoribbons are N-doped with a thickness of two- to seven-layers, have a width of 10–30 nm and length of >1 μm, and show high performance as an anode material for lithium ion batteries. Moreover, this strategy can be readily scaled up for practical applications requiring bulk quantities of graphene nanoribbons.